Cumulative risk and AIDS-orphanhood: interactions of stigma, bullying and poverty on child mental health in South Africa. - Cluver, L; Orkin, M (Elsevier, 2009)
Research shows that AIDS-orphaned children are more likely to experience clinical-range psychological problems. Little is known about possible interactions between factors mediating these high distress levels. We assessed how food insecurity, bullying, and AIDS-related stigma interacted with each other and with likelihood of experiencing clinical-range disorder. In South Africa, 1025 adolescents completed standardised measures of depression, anxiety and post-traumatic stress. 52 potential mediators were measured, including AIDS-orphanhood status. Logistic regressions and hierarchical log-linear modelling were used to identify interactions among significant risk factors. Food insecurity, stigma and bullying all independently increased likelihood of disorder. Poverty and stigma were found to interact strongly, and with both present, likelihood of disorder rose from 19% to 83%. Similarly, bullying interacted with AIDS-orphanhood status, and with both present, likelihood of disorder rose from 12% to 76%. Approaches to alleviating psychological distress amongst AIDS-affected children must address cumulative risk effects.